Sharing Asia's dynamism : Asian direct investment in the European Union (UN New YorkUS, 1996)
Provides an overview of global flows of foreign direct investment from Asia. Examines why Asian investment in Europe is as low as it is. Focuses on the policy implications, given that both Asia and the European Union are interested in raising flows of investments from Asia to Europe.
DC